Speed Breeding: Revolutionizing the Crop Improvement - G., Nagamani; K. R., Yathish; Das, Abhijit K.; C., Susmita; P. L., Soujanaya; J. C., Sekhar (Chronicle of Bioresource Management, 2023)
Feeding our growing population is one of the primary concerns of plant breeders. Plant breeding needs to deliver modern cultivars in a time- and resource-efficient manner. Speed breeding techniques allow breeders to advance crop generation in a shorter period of time. The plants are grown in controlled growth chambers or greenhouses using optimal light intensity and quality, particular day length and temperature, which accelerates various physiological processes in plants. Speed breeding could serve as a basic platform for integrating high-throughput phenotyping and genotyping techniques, marker-assisted/genomic selections, and gene editing for the improvement of the traits in crop species.